Can energy policy drive sustainable land use? Lessons from Biofuels Policy Development over the Last Decade - Woods,J; Kalas,N (Springer, 2013)
The mandated increase in bioenergy as a means to decarbonise our energy supply, enhance energy security, and promote rural development has raised concerns regarding the impacts biomass feedstock production may have on food security and has placed bioenergy feedstock production in competition for resources required to feed a growing global population. Concerns over the direct and indirect impacts of bioenergy, particularly conventional biofuels , have pushed policy makers to try to direct biomass crop production onto marginal, degraded and ‘unused’ land. Moving bioenergy onto ‘marginal lands’ will inevitably raise the costs of feedstock production, but it may also be contradictory to food security where ‘sustainable intensification’ and reduced losses require increased energy inputs. This marginalisation ignores the beneficial role that perennial energy crops could play in managing the sustainable intensification of overall agricultural production required to feed over 9 billion people by 2050. This chapter explores the role and drivers of bioenergy in future world energy production, land use change and wider sustainability issues, and proposes an alternative, integrated approach toward a resource efficient and sustainable provision of agricultural products, including food, feed, biobased chemicals, materials and energy.